The effect of infill structure modification on impact and flexural strength of recycled PET filament in fused deposition modeling - Akmal, Yasir; Widodo, Rahmat Doni; Nuryanta, Muhammad Irfan (JTTM : Jurnal Terapan Teknik Mesin, 2026)
This study investigated the effect of hexagonal, re-entrant, and chiral infill structure modification on the impact and flexural strength of recycled polyethylene terephthalate (PET) filament derived from waste plastic bottles in the fused deposition modeling process. The increasing demand for sustainable materials in additive manufacturing encouraged the reuse of plastic waste as an alternative filament source. An experimental quantitative method was applied by producing recycled polyethylene terephthalate filament and printing test specimens using a three-dimensional printer in accordance with ASTM D256 for impact testing and ASTM D790 for flexural testing. The results showed that the chiral infill pattern produced the highest impact strength value of 0.00982J/mm², indicating superior energy absorption capability under dynamic loading. In contrast, the hexagonal pattern exhibited the lowest impact strength value of 0.00284J/mm². For flexural performance, the unpatterned specimens achieved the highest flexural strength of 14.84MPa, significantly surpassing the patterned specimens due to a larger effective cross-sectional area. In contrast, the hexagonal pattern showed the lowest flexural strength value of 2.16MPa. For the elastic modulus, the unpatterned specimens reached the highest stiffness of 0.27GPa. Conversely, the hexagonal pattern showed the lowest stiffness value of 0.028GPa. These findings affirm the existence of a trade-off between dynamic toughness and static flexural strength depending on the infill design. Therefore, the choice of infill should be adjusted according to the intended mechanical applications of the printed component